A microbiologia no contexto do ensino de ciências e sua inserção no livro didático para os anos iniciais do ensino fundamental. - Ferreira, Roberta Alves da Silva (2023)
The study highlights the relevance of an appropriate and contextualized approach to microbiology for promoting meaningful learning and the construction of conscious and responsible citizenship. The present dissertation aims to use the contents of the science discipline related to microbiology as a didactic reference, analyzing educational guiding documents and their integration into textbooks used in the Initial Years of Elementary Education, in the quest to promote environmental education and sustainable development. In this sense, the inclusion of microbiology in textbooks for the initial years of elementary education serves not only to strengthen students' scientific knowledge but also to stimulate cognitive skills, curiosity, and environmental awareness. As the overall objective, the work seeks to emphasize the importance and the relationship of microbiology in the content of the science discipline, analyzing how it is addressed in educational guiding documents and textbooks used in teaching practice. The research methodology is classified as qualitative, hypothetical-deductive, descriptive, bibliographic, and documentary. The results obtained highlight and assess the skills of the BNCC (National Common Core Curriculum), which directly address content in the field of microbiology. The identified skills and competencies can be associated with health, environmental issues, and sustainability.